2011
DOI: 10.2337/db10-0726
|View full text |Cite
|
Sign up to set email alerts
|

Increased Whole-Body and Sustained Liver Cortisol Regeneration by 11β-Hydroxysteroid Dehydrogenase Type 1 in Obese Men With Type 2 Diabetes Provides a Target for Enzyme Inhibition

Abstract: OBJECTIVEThe cortisol-regenerating enzyme 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) amplifies glucocorticoid levels in liver and adipose tissue. 11β-HSD1 inhibitors are being developed to treat type 2 diabetes. In obesity, 11β-HSD1 is increased in adipose tissue but decreased in liver. The benefits of pharmacological inhibition may be reduced if hepatic 11β-HSD1 is similarly decreased in obese patients with type 2 diabetes. To examine this, we quantified in vivo whole-body, splanchnic, and hepatic 11β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
60
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 48 publications
7
60
1
1
Order By: Relevance
“…This interpretation may be over-simplistic, however, since more chronic reductions in insulin are associated with upregulation of liver 11βHSD1, but no change in adipose 11βHSD1, during low carbohydrate diet in obese men [64]. The concept that chronic hyperinsulinaemia underlies decreased hepatic 11βHSD1 activity in obesity is further supported by the observations described above, that insulin deficiency in patients with type 2 diabetes is associated with higher hepatic 11βHSD1 for the same BMI [4]. It appears likely that insulin itself regulates tissue cortisol regeneration acutely, but that, with chronic alterations in insulin sensitivity, additional regulators of 11βHSD1 come into play, including alternative regulators of metabolism and inflammation.…”
Section: Physiological and Pharmacological Regulation Of 11βhsd1supporting
confidence: 53%
See 3 more Smart Citations
“…This interpretation may be over-simplistic, however, since more chronic reductions in insulin are associated with upregulation of liver 11βHSD1, but no change in adipose 11βHSD1, during low carbohydrate diet in obese men [64]. The concept that chronic hyperinsulinaemia underlies decreased hepatic 11βHSD1 activity in obesity is further supported by the observations described above, that insulin deficiency in patients with type 2 diabetes is associated with higher hepatic 11βHSD1 for the same BMI [4]. It appears likely that insulin itself regulates tissue cortisol regeneration acutely, but that, with chronic alterations in insulin sensitivity, additional regulators of 11βHSD1 come into play, including alternative regulators of metabolism and inflammation.…”
Section: Physiological and Pharmacological Regulation Of 11βhsd1supporting
confidence: 53%
“…glucocorticoid metabolites in urine is elevated in obese people [3], suggesting an increased glucocorticoid production rate, and this has been verified by stable isotope tracer studies in patients with obesity and type 2 diabetes [4]. Moreover, obesity has been associated with impaired negative feedback suppression of the hypothalamic pituitary adrenal axis (HPAA) (by dexamethasone suppression tests) in some [5], but not all [6], studies, and with increased stimulation of cortisol production by adrenocorticotrophic hormone (ACTH) [7].…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Recent studies have demonstrated that whole-body 11β-HSD1 activity is elevated in obese men with type 2 diabetes, whereas liver 11β-HSD1 activity is relatively unchanged, suggesting that disease suppression via 11β-HSD1 inhibition is likely to be more effective in obese patients with type 2 diabetes. 15 Several classes of potent and selective 11β-HSD1 inhibitors have been reported in the literature. 16−26 Some inhibitors, including our own, 16,17 have displayed in vivo efficacy in animal models related to diabetes.…”
mentioning
confidence: 99%